The Potential of the Renminbi as An international Currency - MO, YIN (2012)
The US-originated global financial crisis and the following eurozone sovereign debt crisis have raised questions over the current international monetary system which is built around the US dollar as a global reference currency and the euro as a regional currency. It is increasingly suggested that the global reserve system should better reflect the increased weight of emerging market economies, particularly China, as a natural consequence of its appearance as the world’s new economic powerhouse recently. This paper investigated the potential role of China’s currency, the renminbi, as an international currency. To achieve this goal, an empirical estimation on the determinants of the shares of major reserve currencies held by the world’s central banks was conducted. In addition, the process and achievement of RMB internationalization is assessed to provide relatively clear guidance. The underdevelopment of China’s financial system and persistent constrains on the capital account is thought to be the largest impedence for the renminbi to gain an international role. It is conceivable that China will adopt a gradual and steady path to promote and enhance the RMB’s acceptance overseas without disrupting its own economic development under the consideration of the associated benefits and costs.